2016
DOI: 10.4338/aci-2015-12-ra-0180
|View full text |Cite
|
Sign up to set email alerts
|

Users’ attitudes towards personal health records

Abstract: SummaryBackground: Prevention and management of chronic conditions is a priority for many healthcare systems. Personal health records have been suggested to facilitate implementation of chronic care programs. However, patients' attitude towards personal health records (PHRs) can significantly affect the adoption rates and use of PHRs. Objectives: to evaluate the attitude of patients with Type II diabetes towards using a PHR to manage their condition. Methods: We used a cross-sectional exploratory pilot study. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 16 publications
(18 reference statements)
2
10
0
Order By: Relevance
“…Our results indicated that increasing age is associated with lower odds of using the PHR. This is consistent with the existing literature [44,46,[48][49][50][51]. Even though older patients have more chronic conditions and are in the greatest need of support in disease self-management, many do not use a PHR for a variety of reasons.…”
Section: Principal Findingssupporting
confidence: 90%
See 1 more Smart Citation
“…Our results indicated that increasing age is associated with lower odds of using the PHR. This is consistent with the existing literature [44,46,[48][49][50][51]. Even though older patients have more chronic conditions and are in the greatest need of support in disease self-management, many do not use a PHR for a variety of reasons.…”
Section: Principal Findingssupporting
confidence: 90%
“…Disparities in PHR use by age have frequently been cited in the literature with many studies showing that older individuals are less likely to use a PHR. Confounding factors include low computer literacy, low eHealth literacy, or less inclination to use technology, ultimately leading to more difficulties with advanced technologies such as PHRs [17,32,48]. In a study using a simulated PHR in adults aged 40 years and above, the authors concluded that adults with age-related declines in reasoning and cognitive abilities were more likely to have difficulties completing more complex health management tasks using a PHR [52].…”
Section: Principal Findingsmentioning
confidence: 99%
“…Some PHRs also enable patients to contact others in a similar situation [ 28 , 29 , 83 , 88 ], support groups [ 62 , 87 ], family [ 75 , 89 ], or customer support and billing departments [ 22 ]. Some studies also suggested this function have the ability to maintain a record of past conversations [ 36 ] and provide email or text notification when a health care provider leaves a message on the PHR [ 24 , 93 , 94 ]. Moreover, some studies suggested tracking the status of a question [ 80 ], message multiple providers at the same time [ 24 ], and import selected emails and interactions on the social network to PHRs [ 86 ].…”
Section: Resultsmentioning
confidence: 99%
“…Complicated data entry may cause users to not enter data correctly into their PHR [118]. The reduction and simplification of PHR system data entry should be considered in PHR design [35,93,118]. Users prefer easy to use, simple, and user-friendly interface [24,41,45,54,61,62,65,92,94,110,118,[120][121][122][123][124].…”
Section: Usabilitymentioning
confidence: 99%
“…Interest in personal health management is increasing as aging, and chronic diseases are growing [10]. Recently, active services focused on prevention and health promotion are needed [11] to record life logs such as exercise, food and sleep through various wearable devices [12][13][14] and measure blood pressure, blood sugar, and weight through personal health devices [15].…”
Section: Introductionmentioning
confidence: 99%